Are Epigenetic Mechanisms Involved in Radiation-Induced Bystander Effects? - Mothersill, Carmel (Frontiers in Genetics, 2012)
The “non-targeted effects “ of ionizing radiation including bystander effects and genomic instability are unique in that no classic mutagenic event occurs in the cell showing the effect. In the case of bystander effects, cells which were not in the field affected by the radiation show high levels of mutations, chromosome aberrations and membrane signaling changes leading to what is termed “horizontal transmission” of mutations and information which may be damaging) while in the case of genomic instability, generations of cells derived from an irradiated progenitor appear normal but then lethal and non-lethal mutations appear in distant progeny. This is known as “vertical transmission”. In both situations high yields of non-clonal mutations leading to distant occurrence of mutation events both in space and time. This precludes a mutator phenotype or other conventional explanation and appear to indicate a generalized form of stress induced mutatgenesis which is well documented in bacteria. This review will discuss the phenomenology of what we term “non-targeted effects, and will consider to what extent they challenge conventional ideas in genetics and epigenetics.